IMPROVING MICROLOAN PRACTICES IN THE PROVISION OF RETAIL BANKING SERVICES - Umarova Lola Erkinovna (American Journals, 2025)
The article analyzes the current state and trends in the development of the microcredit system in Uzbekistan. The study examines the interest rates, terms, and methods of providing microloans to the population by commercial banks, as well as the dynamics of the volume of microloans issued to individuals during the period 2020–2024. The research findings indicate that in recent years, the volume of microloans has increased by 7–8 times, which is closely associated with the growth of financial inclusion, the expansion of retail and digital banking services, and the government’s policy of supporting small businesses. The article also highlights the role of the digital lending system in promoting microfinance services and the importance of a risk-oriented approach for commercial banks.
Keywords: Microloan, microcredit, commercial banks, retail banking services, microfinance, financial inclusion, interest rate, credit policy, public welfare, financial stability